Translation is a cultural and human civilizational manifestation, and technical skills for the rapprochement of peoples and nations - Faiz Al-Islam, Jehad (Arab Journal for Sciences and Research Publishing, 2025)
This study aimed to highlight the importance of translation and its tools as a cultural and civilizational manifestation, technical skills and strategy in facilitating the rapprochement of peoples and nations, due to the commonalities between them in terms of humanity, civilization, culture and others, as it enabled them to achieve their goals in all their dimensions, through their openness to other civilizations and through learning about their experiences and creative ideas. It has become difficult to ignore the universality of translation and its important position and its international and international pivotal role, and the tremendous, rapid and amazing developments it has undergone towards the better, with its development as a science, art, practice and theories, which contributed to its cultural role in serving humanity and bringing peoples and nations closer. To achieve the objectives of this study and based on the problem: What about modern translation, its types, arts, skills and theories? What are the developments in it? What is its relationship to civilizations and culture? Based on the descriptive approach, the study concluded that: Translation is a fundamental pillar in the development of civilization and culture, and before being a skill and an art, it is a culture to strengthen the relationship between peoples. Also, the science of translation needs to find a balance between the theoretical aspect and the aspect of skill, science and practice. The important goal of this research is to contribute to enriching the translation library, even if it is small, and to serve humanity.